Macromedia flash mx 2004 - Underdahl, Brian ([S.l.] : McGraw-Hill Osborne Media, 2003)
Animate your productions and publish Flash movies. Take advantage of Flash$1 (Bs functionality and flexibility, and discover even greater creativity and brighter, more effective Web content. Get fascinating, step-by-step coverage of arguably the most exciting Web authoring tool ever created. Learn the fundamental tools as well as ActionScript, Flash$1 (Bs native programming languas
Keywords: a